Analisis Gaya Bahasa dalam Acara Stand Up Comedy Season 10 di Kompas TV - Asnayanti Asnayanti; Hasriani Hasriani; Asis Nojeng (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the forms and functions of figurative language in Stand Up Comedy Indonesia Season 10, as well as their implications for audience reception. This study uses a descriptive qualitative approach with stylistic and pragmatic perspectives on comedians' humorous utterances sourced from 24 videos on the Kompas TV YouTube channel. The results indicate that there are four main forms of figurative language: comparison, affirmation, opposition, and satire, with satire, particularly irony, dominating. Functionally, figurative language is used to enhance the story's appeal, create humorous effects, build emotional closeness, strengthen the comedian's identity, and convey social criticism, with humor being the most dominant function. These findings indicate that figurative language plays a role not only as an aesthetic element but also as a pragmatic strategy in creating rhetorical effects through deviations in meaning, reversals of expectations, and the conveyance of implicit meanings. Thus, the effectiveness of humor in stand-up comedy is determined by the synergy between stylistic and pragmatic aspects that shape audience responses and interpretations.